Pengaruh Kualitas Pelaksanaan Program Musyawarah Guru Mata Pelajaran Terhadap Peningkatan Kompetensi Profesional Guru Fisika Tingkat SMA - Sari, Nurmala; Purbani, Widsyastuti (Pattimura University, 2023)
The aim of the research is to determine the influence of the quality of the implementation of the subject teacher deliberation program on increasing the professional competence of physics teachers at the high school level in Aceh Jaya Regency. The method used in this research is a sequential explanatory design (QUAN-qual). Quantitative research methods use survey methods with ex post facto research. Qualitatively using the phenomenographic method through observation, interview and documentation techniques. The sampling technique was carried out by random sampling, specializing in 40 physics education teachers at the high school level. The instruments used were questionnaires and interview guidelines. The data analysis technique uses a simple linear regression test and hypothesis testing assisted by the SPSS version-22 application. The research results show that there is an influence on the quality of the implementation of the MGMP program on increasing the professional competence of high school physics teachers in Aceh Jaya Regency. The test results prove that tcount > ttable or 7.265 > 2.024, then the significance value is 0.000 < 0.05. The results of the interview show that this MGMP activity is able to improve teachers' professional competence, because MGMP is a forum for communication between fellow physics teachers in solving learning problems, both regarding media, methods and learning models that are suitable for the problems experienced by the teacher.